Experimental Research on Solar and Geothermal Energy Coupling Power Generation System. (February 2019) - Song, Anda; Zhu, Jialing; Zhang, Peipei; Chang, Nini; Cui, Zhiwei
Abstract: A mathematical model for the efficiency of the collector and the temperature of the heat transfer oil is established on the basis of heat transfer characteristics of the trough solar collector. A solar geothermal energy coupled ORC power generation experiment platform is established, and the thermodynamic performance of the system is simulated using MATLAB. The net output power and thermal efficiency of the single geothermal power station and the solar geothermal energy coupled power station are calculated in accordance with the change of solar radiation in one day under solar radiation intensity and environmental temperature in Lhasa. The efficiency of the collector increases with the increase of the solar radiation intensity, the maximum efficiency theory can be 0.553 and the experiment can be 0.532, as the theory and results suggest. The thermal efficiency of the coupled power station is 11.21% larger than that of the single air cooled geothermal ORC power station, which makes up the adverse effect of the temperature rise in the daytime, as the hourly calculation results.